2020
DOI: 10.1002/alz.12168
|View full text |Cite
|
Sign up to set email alerts
|

The competing risk of death and selective survival cannot fully explain the inverse cancer‐dementia association

Abstract: Introduction: We evaluated whether competing risk of death or selective survival could explain the reported inverse association between cancer history and dementia incidence (incidence rate ratio [IRR] ≈ 0.62-0.85). Methods: A multistate simulation model of a cancer-and dementia-free cohort of 65year-olds was parameterized with real-world data (cancer and dementia incidence, mortality), assuming no effect of cancer on dementia (true IRR = 1.00). To introduce competing risk of death, cancer history increased mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
1
13
2
Order By: Relevance
“…This observed protective effect of cancer against dementia is largely in line with previous research 1,4,10,22,23 . For example, a recent prospective cohort study found that individuals diagnosed with cancer during follow‐up had a 3‐fold reduction in risk of AD 4 .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This observed protective effect of cancer against dementia is largely in line with previous research 1,4,10,22,23 . For example, a recent prospective cohort study found that individuals diagnosed with cancer during follow‐up had a 3‐fold reduction in risk of AD 4 .…”
Section: Discussionsupporting
confidence: 83%
“…This observed protective effect of cancer against dementia is largely in line with previous research. 1 , 4 , 10 , 22 , 23 For example, a recent prospective cohort study found that individuals diagnosed with cancer during follow‐up had a 3‐fold reduction in risk of AD. 4 Recent meta‐analyses similarly reflect a protective effect in extant literature, estimating an overall pooled effect size associated with a 15% to 37% decrease in risk of AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may explain counterintuitive results, where exposures that are known to be harmful for mortality risk, such as smoking [4,5] or history of cancer [6], sometimes seem protective for the risk of dementia. Authors have attempted to make sense of these counterintuitive results by naming biases such as "competing risk bias" or "survival bias" [7,8]. However, the bias associated with a particular analytic method cannot be defined or assessed if the causal question is not explicitly specified.…”
Section: Introductionmentioning
confidence: 99%